Calf muscle injury in elite athletics: an 8-season prospective cohort study - Kelly, S.; Polglass, G.; Giakoumis, M.; Pollock, N.; Shaw, J. W. (Journal of Science and Medicine in Sport, 2025)
Objective To describe epidemiological data of indirect calf muscle injury (CMI) in elite track and field athletes. To investigate relationships between CMI and athlete characteristics to inform future injury prevention strategies.